Improving Self-Efficacy of Non-Music Specialist Teachers in Primary Schools Through Teacher Training Program: An Action Research in Indonesia - Vassiyevna, Salomova Rano; Julia, J.; Supriyadi, Tedi; Gunara, Sandie; Agustian, Egi; Omonovich, Khimmataliev Dustnazar; Dustnazarovna, Omonova Mukhlisa (Universitas Pendidikan Indonesia, 2025)
This study investigates the enhancement of self-efficacy among non-music specialist primary school teachers in Indonesia through a targeted training program. Many primary educators, particularly those without formal music training, often lack confidence in their musical abilities, which limits their willingness to teach music. Using an action research design, the program was implemented in three stages—pre-action, action, and post-action—aimed at improving teachers’ competence and confidence in music instruction. Twenty-eight teachers from Sumedang Regency, West Java, participated, representing diverse demographics in certification status, age, employment type, teaching grade level, and years of experience. The training included workshops, collaborative reflections, teaching simulations, and practical sessions on integrating music into classroom activities. Quantitative data from pre- and post-tests, along with qualitative observation notes, revealed significant gains in all self-efficacy dimensions, with the overall mean score increasing from 3.3 to 4.3 (p 0.001) and a very large effect size (d = 2.5). Notable improvements were observed in developing higher-order thinking skills, assessing students’ understanding of music, and fostering the value of music learning. The findings underscore the importance of sustained, practice-based professional development to build teacher confidence, promote innovative pedagogy, and integrate music meaningfully into primary curricula. This research highlights the necessity of equipping non-specialist teachers with pedagogical strategies and personal empowerment to strengthen music education frameworks and improve student learning experiences in primary schools.